Symptomatology and development of banana streak badnavirus, under natural conditions in Ibadan, Nigeria - Hughes, J.; Gauhl, F.; Pasberg-Gauhl, C.; Dahal, G. (International Society for Horticultural Science, 2000)
A field experiment with suckers taken from five improved plantain hybrids and one landrace with typical symptoms of banana streak badnavirus (BSV) infection was established at Ibadan (Nigeria) to investigate climatic factors affecting BSV symptom development and to identify parameters useful in genotype evaluation for BSV incidence. Weekly monitoring of individual plants for symptom incidence and severity indicated that symptom expression was more severe during the rainy season (July to October-November) than in the dry season (January to May-June). Symptoms included discrete yellow streaks on the leaves, internode shortening with rosette-like leaves, a necrotic cigar leaf and distorted (inverted) bunch. An evaluation of these symptoms and their grouping indicated that chlorotic streaks or oval to spindle-shaped lesions were predominant in most genotypes. Appearance of symptoms varied both within and between accessions. On TMPx 7002-1 and TMPx 548-9 the BSV symptoms were first observed about 80 days after transplanting (DAT), whereas for Agbagba, TMPx 548-4, TMPx 4698-1 and TMPx 2796-5, the symptoms were first observed more than 100 DAT. The final percentage of BSV-symptomatic plants was generally high (> 50%) on both the hybrids and the landrace Agbagba but TMPx 548-9 and TMPx 7002-1 had more than 80% symptomatic plants. Irrespective of genotype, symptomatic mother plants produced a higher percentage of mats where all suckers showed BSV symptoms than did asymptomatic mother plants. During the hot season, approximately 70% of the symptomatic plants and 15% of the asymptomatic plants indexed positive for BSV by enzyme-linked immunosorbent assay. Disease progress curves for temporal development of banana streak symptoms were sigmoid. The increase in incidence of symptomatic plants was best described by the Gompertz model. Statistical analysis of the parameters associated with the disease progress curves suggested that besides symptom incidence other parameters such as area under the disease progress curve and rate of symptom development were essential for evaluation of Musa accessions for BSV incidence.